CHARACTER EDUCATION CONTENT IN LEARNING HISTORY IN YOGYAKARTA SMA IT ABU BAKAR - Deni Rakhman; Djoko Suryo (ISTORIA: Jurnal Pendidikan dan Sejarah, 2018)
The purpose of the research is to revealthecontent of character educationin historical learning in SMA IT Abu bakar Yogyakarta. This research used the qualitative approach method and descriptive starting from January to April 2016. Data was collected by observation, interview, document review and questionnaireto obtain data on the activities of character education transformation in historical learning, Interviewwas used to get data on the implementation strategy of character education in historical learning, meanwhile research documents such as program to complement the observations and interviews.Questionnaire is to determine the extent of educational character in historical learning which can shape students's character.Technique inspection and validity of the data means of triangulation of data and data analysis techniquesqualitatively. The results of this research are as follows. (1) SMA IT Abu Bakar Yogyakarta has vision and mission which become a superior schoolin integrationIMTAQ and IPTEK to support the vision and the mission of the values that instilled in the school. (2) In the planning of historical learning refersto the value of character by Dinas adjusted to 10 muwashofat or 10 Muslim personalitywereowned by SMA IT Abu Bakar Yogyakarta. (3) In the process of reviewing learning in each to know the values of characters that can be appeared in the. (4) Assessment of teaching history applying for existing guidelines point to cognitive character values. (5) The barriers in learning history because the lack of whole comprehension and completely toward integrated Islamic school.Keywords: the substance, character education, learning history